PERS sebagai Sarana Dakwah - Efendi, Erwan; Amanda, Salsabilla; Marwansyah; Ardana, Riau; Dari, Wulan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The aim of tis research is to find out how the press can be used as a means of preaching. The method used in this research is a literature review research method by collecting various journal, article and book references. From the results of this research, it is known that the press has a very large influence when used as a means of da’wah. the press is able to influence public opinion, so that when used as a means of da’wah the press is able to achieve the goals of da’wah.